Introduction to intelligent surveillance - Yan, Wei Qi (Springer International Publishing AG 2017, 2017)
This accessible textbook/reference reviews the fundamental concepts and practical issues involved in designing digital surveillance systems that fully exploit the power of intelligent computing techniques